Economic and Social Upgrading Dynamics in Global Manufacturing Value Chains: A Comparative Analysis - Thomas Bernhardt; Ruth Pollak (FIW - Research Centre International Economics, 2015)
Recent decades have witnessed an increasing integration of developing countries into global value chains (GVCs). This growing participation in global production sharing has raised hopes for economic upgrading within such value chains. However, globalization has intensified international competition, and achieving economic upgrading is not an easy task. Moreover, the social consequences of participating in GVCs are not always positive; however, they have received considerably less attention in the literature. This paper suggests a simple and parsimonious approach to measuring economic and social upgrading (and downgrading) in GVCs. Applying this parsimonious methodology and using quantitative secondary data, we analyze how widespread upgrading has been in four selected manufacturing GVCs: apparel, wood furniture, automotive, and mobile phones. We also investigate to what extent downgrading is part of the reality and undertake a comparative analysis across GVCs, regions and country groups (developing vs. developed countries). We find that the promise of industrial upgrading through participation in GVCs does not materialize for everyone. Indeed, economic upgrading has taken place in just over a quarter of the countries in our sample, among them mainly developing countries. Finally, we examine the relationship between economic performance and social performance in the different GVCs to investigate whether or not economic upgrading is typically associated with social upgrading. While patterns differ across GVCs, we find that economic upgrading is more likely to occur simultaneously with social upgrading than without, and vice versa. Our analysis, thus, suggests that economic upgrading is conducive to, but not sufficient for, social upgrading to occur.
Keywords: F14; F63; F66; O19; O57; 330; global value chains; economic upgrading; social upgrading; apparel; automotive; mobile phones; wood furniture